Experimental evidence of a delta-shock in nonlinear chromatography - Mazzotti, Marco; Tarafder, Abhijit; Cornel, Jeroen; Gritti, Fabrice; Guiochon, Georges (Journal of Chromatography A, 2010)
We report about a new type of composition front in nonlinear chromatography that is called delta-shock, which has to be added to the family of classical transitions, i.e. simple waves, shocks and semi-shocks. Recently, the occurrence of delta-shocks in the case of mixed competitive-cooperative isotherms of the following type n i = H i c i 1 − K 1 c 1 + K 2 c 2 ( i = 1 , 2 ) , (with H 2 > H 1 , where components 1 and 2 have anti-Langmuir and Langmuir adsorption behavior, respectively) was predicted theoretically and their behavior was analyzed in the frame of the equilibrium theory of chromatography. The delta-shock can be viewed as a growing traveling spike superimposed to the discontinuity separating the initial and the feed state, which propagates along the column at constant speed and constant rate of growth. In this work we complement these findings from an experimental point of view. The binary system consisting of phenetole (component 1) and 4-tert-butylphenol (component 2) in methanol–water (about 2:1, v/v) on a Zorbax 300StableBond-C18 column from Agilent has been shown, through a series of overloaded pulse experiments and of frontal analysis experiments with the pure compounds, to be subject to the competitive-cooperative isotherm of the type above, up to rather large concentrations. This system does exhibit a delta-shock when the operating conditions are chosen according to theory, namely when phenetole initially saturating the column is displaced by 4-tert-butylphenol, both at high concentrations (the minimum concentrations exhibiting a fully developed delta-shock in this series of experiments were c 1 = 20 g/L and c 2 = 75 g/L). The propagation of the delta-shock matches the theoretical predictions in terms of both the effect of concentration and the effect of column length. This is the first experimental observation ever of a delta-shock in chromatography. It is noteworthy that the proof of the occurrence of the delta-shock reported here has been obtained in both laboratories cooperating in this project.